SCAFFOLDING IN TEACHING WRITING - Listiana Ikawati (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2020)
AbstractAs one of the prominent skills in English language learning, mastering writing is a must for students at various educational levels, yet many of them sometimes have difficulties in generating ideas, using grammar and vocabularies and maintaining unified ideas in their writing. Considering the problems faced by the students and practices needed by students to improve their writing skills, the teachers can use scaffolding strategy derived from Vygostky’s ZPD theory. It is believed that students can complete the difficult task that is a bit higher than their ability through guidance from more expert others. The purpose of the study was to figure out how scaffolding can be used to improve students’ writing skills. The results of the study show that scaffolding can be used as teacher’s strategy to improve students’ writing skills by integrating the writing process in the genre-based approach representing the scaffolding. It shows how the teacher gradually removes his assistance as soon as students have the experience for completing the task. Through scaffolding, students will learn how to experience the strategy, rather than merely to complete the task and it leads them to be autonomous and successful writers.Keywords: Scaffolding, writing, and ZPD